2021
DOI: 10.1002/vetr.302
|View full text |Cite
|
Sign up to set email alerts
|

Influence of farm management on the dynamics of Salmonella enterica serovar Infantis shedding and antibiotic resistance during the growing period of broiler chickens

Abstract: Background: Salmonella enterica serovar Infantis is a zoonotic pathogen isolated in broilers causing great economic losses in the European poultry sector. It is demonstrated that an investment in management measures at farm level could directly affect the control of food chain microorganisms. The aim of this study was to investigate the development of S. Infantis antimicrobial resistance (AMR) patterns during the growing period, according to flock density and ventilation management, without antibiotic administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Although Dutch national statistics reported lower AMU in farms with "alternative" chicken breeds associated with less intensive systems (Van Geijlswijk et al, 2019), an experimental study of fast-and slow-growing broiler breeds with no antimicrobial treatment showed a similarly high rate of AMR in both groups (Montoro-Dasi et al, 2020). The same authors observed rapid development of resistance without any AMU in another experiment, and found no significant differences in AMR between groups with high and low stocking density or groups with different levels of ventilation (Montoro-Dasi et al, 2021).…”
Section: Indoor and Free-range Systemsmentioning
confidence: 98%
“…Although Dutch national statistics reported lower AMU in farms with "alternative" chicken breeds associated with less intensive systems (Van Geijlswijk et al, 2019), an experimental study of fast-and slow-growing broiler breeds with no antimicrobial treatment showed a similarly high rate of AMR in both groups (Montoro-Dasi et al, 2020). The same authors observed rapid development of resistance without any AMU in another experiment, and found no significant differences in AMR between groups with high and low stocking density or groups with different levels of ventilation (Montoro-Dasi et al, 2021).…”
Section: Indoor and Free-range Systemsmentioning
confidence: 98%
“…A predominant clone in European broiler production was found to be resistant to ciprofloxacin/nalidixic acid, sulfamethoxazole, and tetracycline. Additionally, a considerable percentage of S. Infantis strains (45.3%) demonstrated MDR, and the production of ESBL enzymes was also frequently observed [4,15,35,42,48,49].…”
Section: Salmonella Infantis: the Current Challengementioning
confidence: 99%
“…Additionally, a considerable percentage of S . Infantis strains (45.3%) demonstrated MDR, and the production of ESBL enzymes was also frequently observed [ 4 , 15 , 35 , 42 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fourth is automatic loading. Spring Boot [30] scans all beans in the path where the startup class is located by default, and automatically configures beans for package/class jars in the project classpath, which greatly simplifies the work.…”
Section: Microservice Architecture Designmentioning
confidence: 99%